Strategic Approaches for Elevating Room Service Quality at Hotel Asa Larantuka, East Flores Regency - Roncally, Fatima Maria Deinse; Susila, I Made Gede Darma; Wulandari, Pande Putu (Language Assistance, 2024)
Room service quality improvement strategy is one of the strategies applied by a hotel to increase the number of guests. The purpose of this research is to find out the quality of room service that has been done and the right strategy used to improve the quality of room service at Hotel Asa Larantuka. This research uses a descriptive qualitative approach with observation, interview and documentation techniques. The quality of room service at Hotel Asa Larantuka can be known through interviews with parties such as: hotel employees, guests and government. Interview indicators with reference to the five dimensions of service quality. The results of this study obtained the strategy used to improve the quality of room service is SWOT matrix analysis, among others: 1) Strategy (SO), which is a strategy carried out by the hotel by maintaining all facilities and maintaining the cleanliness of the hotel and providing a good appearance of the employees, 2) Strategy (WO), by improving employee skills in service 3) Strategy (ST) is a strategy to respond quickly to guest complaints and 4) Strategy (WT) is a strategy by always communicating with guests. Suggestions for managers are to maximise the quality of services that have been carried out and improve the shortcomings that are owned in accordance with the strategies that have been prepared. This is expected to improve the quality of service provided and provide satisfaction to tourists who stay overnight so that they make return visits in the future.